2022
DOI: 10.1161/circheartfailure.121.008362
|View full text |Cite
|
Sign up to set email alerts
|

The RAISE Trial: A Novel Device and First-in-Man Trial

Abstract: Background: Currently, standard medical therapies have limited effects on heart failure with preserved ejection fraction (HFpEF), which impacts on the life quality and survival of patients. This study aimed to evaluate the safety and efficacy of the percutaneous radiofrequency ablation–based interatrial shunting for HFpEF with a novel atrial septostomy device. Methods: A preclinical study in 11 normal domestic pigs and the first-in-man study in 10 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In the experimental proof of concept, the intervention appeared safe with sustained patency and no thromboembolic or other complications. The first-in-human experience, limited to 10 patients, demonstrated early feasibility and favourable changes in surrogate efficacy parameters; however, shunt narrowing over time was reported in the majority of patients 27 . An additional clinical programme is under development to evaluate the efficacy and safety of this approach in a larger patient population.…”
Section: Noya: Adjustable Interatrial Shunt Devicementioning
confidence: 99%
“…In the experimental proof of concept, the intervention appeared safe with sustained patency and no thromboembolic or other complications. The first-in-human experience, limited to 10 patients, demonstrated early feasibility and favourable changes in surrogate efficacy parameters; however, shunt narrowing over time was reported in the majority of patients 27 . An additional clinical programme is under development to evaluate the efficacy and safety of this approach in a larger patient population.…”
Section: Noya: Adjustable Interatrial Shunt Devicementioning
confidence: 99%
“…PCWP was reduced at 100 days (− 9 mmHg;) with diminished LA-to-RA gradients (− 10 mmHg) 2 deaths (20%) during follow-up (one at 221 days and the other at 450 days). No HFH (median follow-up 261 days) Radiofrequency ablation–based interatrial shunt Sun et al, Circulation: Heart Failure (2022) [ 67 ] First-in-man trial n = 10 (90%) HFpEF or HFmrEF with NYHA functional classes II–IV and at least one HFH during the last years though OMT, NT-proBNP > 200 pg/mL (or > 600 if AF) and LAP > 15 mmHg Primary endpoints: SADE and interatrial shunt performance. Secondary endpoints: HFH and the change in clinical functions at 6 months No SADE during the whole study (100%) Shunt could still be observed in 7 patients at 6 months (2 patients showed the closure and 1 patient missed follow-up).…”
Section: The Role Of Left Atrial Pressure and The Rationale For The D...mentioning
confidence: 99%
“…After ablation, the device was removed from the body, leaving nothing but an artificial ASD [ 59 ]. This novel approach was evaluated first in 11 domestic pigs and then in 9 HFpEF patients and 1 with HFmrEF with NYHA functional classes II–IV [ 67 ]. RAIAS therapy was successfully administered to all patients, and an evidence interatrial left-to-right shunt flow was detected with a mean Qp:Qs of 1.3 ± 0.3.…”
Section: Novel Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 2019 3 mo HFrEF/HFpEF, NYHA Class −1.4/−1.1; KCCQ ↑16/↑ 20; 6MW ↑ 30/↑ 26 m; PCWP ↓2/↓5 mm Hg; Qp:Qs 1.3/1.1 Occlutech AFR PROLONGER study, AFteR registry Currently enrolling NoYa Pilot Single arm (EF >35%) 10 Lotan 2019 1-3 mo Shunt diameter 3-4 mm; 6MW ↑ 56 m; BNP ↓ 1878 pg/mL NoYa RAISE trial Single arm 10 Sun et al. 29 2022 3/10 shunts closed by 6 mo in pigs; 3/10 shunts closed at 6 mo in humans Alleviant HF-1, HF-2, HFrEF Single arm, 28 HFpEF, 5 HFrEF 33 total Preliminary data presented at THT, TVT and SCAI meetings 2022 7 mm shunt; no implant; 100% patency 6 mo; ↓ ex PCWP; ↑6MW; Ongoing f/u. Edwards Life Sciences ALt FLOW Single arm 15 Recruiting Pivotal trials Corvia REDUCE LAP-HF II Double-blind RCT (EF >40%) 626 Shah et al.…”
Section: Existing Data On Atrial Shuntsmentioning
confidence: 99%